Impact of the IDF-DAR Risk Stratification and Pre-Ramadan Education on Diabetes-Related Complications - Reesi, Ali Al; Reesi, Hamed Al; Ghaithi, Salem Al; Ali, Ibrahim Al; Siyabi, Sheikha Al; Balushi, Salwa Al; Kumar, Ameet; Maqbali, Maryam Al; Eidi, Malouk Al; Ali, Khalid Mohammed (Journal of Diabetes and Endocrine Practice, 2025)
Ramadan, the ninth month of the Islamic lunar calendar, requires Muslims to fast from dawn to sunset. However, fasting during this holy month can be challenging, particularly for individuals with chronic diseases like diabetes mellitus.This study aims to assess the validity of the new International Diabetes Federation-Diabetes and Ramadan International Alliance (IDF-DAR) risk stratification tool for Ramadan fasting in predicting persons with diabetes' ability to fast safely and assess the impact of well-structured pre-Ramadan education in helping patients to fast safely and reducing fasting-associated complications.This prospective observational study was carried out in three diabetes centers in Oman from January to March 2024. All eligible patients seeking diabetes care in the study settings were invited. They were provided with a prefasting risk assessment and introduced to a well-structured educational program with a follow-up during and after Ramadan to record progress conditions. Variables were statistically described, and the hypotheses were tested at a 5% significance level using SPSS, version 23.IDF-DAR stratification revealed a significant difference in diabetes type and a significant correlation with hemoglobin A1c levels. Half (51%) of patients with type 1 diabetes mellitus managed to fast the entire month compared to the majority (89%) of those with type 2 diabetes mellitus. Breaking the fast was more often associated with hypoglycemia (37%) and hyperglycemia (20.5%). Only 1.9% of patients required hospitalization during Ramadan, mainly due to diabetic ketoacidosis.The IDF-DAR risk stratification has proven to be a reliable and valid tool for predicting the risk of adverse fasting events in patients with diabetes. Pre-Ramadan education plays a vital role in minimizing fasting-related complications.
Keywords: diabetes; Ramadan; IDF-DAR risk stratification; hypoglycemia; hyperglycemia; DKA